Pengembangan Ekosistem Halal melalui Sertifikasi Halal Skema Self-Declare pada UMKM di Desa Alamendah - Neneng Windayani; Andina Zakia Zahra; Nisrina Salma Mardiah; Syahid Aziz Ibrahim (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
The need for halal products in Indonesia, as the country with the world's largest Muslim population, holds undeniable significance. To support this, KKN themed on Halal Studies by UIN Bandung through the Halal Studies Center has implemented a support program aimed at facilitating Micro, Small, and Medium Enterprises (MSMEs) in obtaining halal certification. This community engagement activity is an integral part of the program, with a primary focus on entrepreneurs in Desa Alamendah, Rancabali, Kabupaten Bandung. In its implementation, there are four key stages carried out in this community engagement activity. The first stage involves training KKN participants as assistants in the halal certification process. The second stage includes the socialization of halal certification to entrepreneurs in Desa Alamendah. The third stage entails providing assistance in developing a halal assurance system in accordance with established standards. Finally, the fourth stage involves offering technical guidance in the halal certification application process. The results of this activity are highly significant, as they contribute to raising awareness among the public about the importance of halal product assurance. This also provides valuable support for government programs and the Halal Studies Center at UIN Bandung in their efforts to promote halal certification for MSMEs. Thus, this article reflects a crucial contribution to strengthening the halal ecosystem and promoting halal products in Indonesia, with a focus on empowering MSMEs in Desa Alamendah.